Abordagem educativa para o uso de medicamentos em remanescentes quilombolas: uma perspectiva Freiriana - Morbeck, Natália Belo Moreira (Universidade Federal do Tocantins, 2017)
The Indiscriminate use of drugs has become a world leading public health problems , especially for the old , for being the most medicalized age population. The goal of this study was to identify the dimensions that influence the rational use of drugs in an elder Quilombolas remnants population through an educative approach based on Freire’s thoughts, in the community of Malhadinha located in the city of Brejinho de Nazaré – Tocantins. A Descriptive Study, of quantitative and qualitative nature, this verification occured through semi-structured interviews and a sensibilization as required, nominated by educative intervention. Participated in the study Quilombolas remnants over 60 years, academics from the Malhadinha pole of Universidade da Maturidade of the Universidade Federal do Tocantins in the city of Brejinho de Nazaré – TO. The results showed high elderly rate in the illiterate group (46.2%) and 1-4 years of education (34.6%). It is evident that the act of self-medication is relevant among the participants as well as the careless treatment, the use of non-prescription drugs and the improper drug disposal. It may also happen prescription leavers and the drug use indicated by family and friends. Supports that the storage and drugs disposal occurs inappropriately. Noteworthy is the search of information through the TV and difficult acces to health care. As for the drugs reported by the participants, 21.21% are included in the Beers-Fick Criteria. We conclude that the booklet proposed in this research will contribute to build a more prepared society to critically face the linked information on health care and medicines. Corroborating to the development of healthy habits, encouraging the rational drug use, without submerging the essence of Quilombola culture, not only respecting differences, but adopting the Paulo Freire’s concepts, comprising as a cultural enrichment in which everyone can learn and develop.